THE INFLUENCE OF INTERACTIVE MEDIA ANIMATI OF VIDEO SYMBIOSIS EXPLORATION MATERIAL ON STUDENTS’ LEARNING OUTCOMES - Anis Rahma Fitara; Dian Nuzulia Armariena; Marleni (Esteem Journal of English Education Study Programme, 2024)
This research is motivated by the low learning outcomes when learning science. This is evidenced by learning outcomes that do not reach the KKM score, as well as the use of monotonous media such as theme books, so that students have difficulty understanding the material and making learning less meaningful. The purpose of this study was to determine whether or not there was an effect of interactive media, animated videos, symbiosis exploration material on science learning outcomes in grade V SDN 34 Palembang. This research is a type of experimental research, namely the Quasi experimental type. The population and sample in this study were fifth grade students of SDN 34 Palembang, totaling 30 students in the control class and 30 students in the experimental class. Data collection techniques in this study were observation, tests and documentation. Data analysis techniques in this study include normality test, homogeneity test, hypothesis testing. The results of the study are hypothesis testing shows t count> t table or 6.491> 1.672 so it can be concluded that H0 is rejected and Ha is accepted. This means that there is an effect of interactive media, animated videos, symbiosis exploration material on the learning outcomes of fifth grade students of SDN 34 Palembang.